2018
DOI: 10.9758/cpn.2018.16.3.246
|View full text |Cite
|
Sign up to set email alerts
|

Microglia and Autism Spectrum Disorder: Overview of Current Evidence and Novel Immunomodulatory Treatment Options

Abstract: Autism spectrum disorder is a rapidly increasing heterogeneous neurodevelopmental syndrome, remarked by persistent deficit in social communication, and restricted, repetitive patterns of behavior and interest. Lately, maternal immune activation and micgroglial dysfunction in the developing brain have been gaining mounting evidence and leading to studies of various novel agents as potential treatment options. A few immunomodulatory treatment options—luteolin, minocycline, suramin, vitamin D, gut microbiota—are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…Despite the enigma of the exact pathogenesis of ASD, numerous studies have indicated that neuroinflammation might be one of the key factors for its development. The latter is assumed because activated microglia take part in the elimination of redundant synapses, a process known as synaptic pruning [109,110]. Thus, we believe that TSPO as a regulator of neuroinflammation and neuronal development may be involved in ASP.…”
Section: Tspo In Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
“…Despite the enigma of the exact pathogenesis of ASD, numerous studies have indicated that neuroinflammation might be one of the key factors for its development. The latter is assumed because activated microglia take part in the elimination of redundant synapses, a process known as synaptic pruning [109,110]. Thus, we believe that TSPO as a regulator of neuroinflammation and neuronal development may be involved in ASP.…”
Section: Tspo In Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
“…Several studies in human and animal models of ASD revealed the presence of an enhanced level of pro-inflammatory cytokines, brain-specific auto-antibodies in the cerebrospinal fluid and serum, illustrating an elevated immune response substantiating the fact that immune dysregulation acts as a key factor contributing to the pathophysiology of ASD [58,59]. Further autopsy of the brain specimens of ASD patients showed the presence of activated microglial cells, together with an increased level of cytokine, such as interferon (IFN)-γ, IL-1β, IL-6, IL-12p40, tumor necrosis factor (TNF)-α and chemokine C-C motif ligand (CCL)-2 [60,61]. Elevated cytokines and chemokines were related to aberrant stereotypical behavior and cognitive impairment.…”
Section: Gut Microbiome-associated Immune Deregulationmentioning
confidence: 88%
“…These glia are found at all stages of brain development. 19 About 50% of all neurons in the developing brain undergo programmed cell death. Corpses are phagocytized by microglia throughout life.…”
Section: Astrocytes and Microglia (Cns)mentioning
confidence: 99%